Relationship of The Military Prosecutor General And The Attorney General in The Prosecution Function - Hedwig Adianto Mau; Ani Afrilda Sinaga; Maria Anna Samiyati (The Southeast Asia Law Journal, 2016)
Law enforcement is a process to translate the wishes of the law into reality. The law enforcement process will culminate in the implementation of laws and regulations by the law enforcement officers themselves. Law enforcement agents in the Indonesian public criminal justice system include: Police, Prosecutors, Judges, Lawyers, and Penitentiaries. Meanwhile, law enforcement agents in the Indonesian armed forces criminal justice system include: Military Judges, Military Prosecutors, Military Police, Military Defense Attorneys, and Military Penitentiaries. Elucidation of Article 57 of Law Number 31 of 1997 stipulates that the Military Prosecutor General in performing prosecution function shall be responsible to the Attorney General of the Republic of Indonesia as the highest public prosecution service in the State of the Republic of Indonesia through the Commander-in-Chief, while in performing duties to develop the Military Prosecution Service, shall be responsible to the Commander-in-Chief. Although the Law Number 31 of 1997 has governed the relationship between the Military Prosecutor General and the Attorney General in performing their duties in technical prosecution function, but in the practice, those duties have not been performed as mandated by a statutory law. Keyword: Law Enforcement in Prosecution Function